Low-density polyethylene cracking method and cracked gasoline
By using a specific ZSM-5 molecular sieve catalyst to perform low-density polyethylene pyrolysis under conditions without precious metals and external hydrogen, the problems of low liquid phase yield and low calorific value were solved, enabling the efficient upgrading of polyolefin plastics into liquid fuel and reducing catalyst costs.
Patent Information
- Application Number
- CN202511030459.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-11-04
AI Technical Summary
In existing low-density polyethylene pyrolysis technologies, the liquid phase yield and calorific value need to be improved, and the catalysts are expensive, with precious metal catalysts being the most common choice.
Using a specific ZSM-5 molecular sieve as a catalyst, low-density polyethylene was cracked under conditions without precious metals and external hydrogen. The silicon-aluminum molar ratio was 20-100, and the ZSM-5 molecular sieve catalyzed the cracking under specific peak intensity ratio ranges in the X-ray diffraction pattern. The cracking was carried out at 380-420℃ in an inert atmosphere of 0.5-1MPa.
It achieves low-density polyethylene pyrolysis with high liquid phase yield and high liquid phase combustion calorific value, and upgrades polyolefin plastics into liquid fuel under mild conditions, reducing catalyst costs.
Smart Images

Figure CN120888323A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of low-density polyethylene pyrolysis technology, specifically to a method for pyrolyzing low-density polyethylene and pyrolyzed gasoline. Background Technology
[0002] In 2014, approximately 311 million tons of plastic were produced globally, and it is projected that over 500 million tons of waste plastic will be generated by 2050, causing severe environmental pollution and resource crises, and even causing significant damage to ecosystems through biological cycles. Currently, plastics are mainly recycled mechanically, typically through collection, sorting, and washing before being reprocessed into new products; however, according to relevant literature, the recycling rate is only 2%. Among various plastics, polyolefins have the largest global consumption, accounting for more than half of the commodity market. PE is polymerized from inert C-C bonds, possessing high molecular weight and easily entangled long chains, exhibiting high thermodynamic stability, and its thermal fracture occurs through random fracture, making it highly difficult to degrade.
[0003] Catalytic conversion is a reasonable method to transform plastic waste into high-value-added products. Commonly used catalysts include mixtures of Pt / WO3 / ZrO2 and Y molecular sieves, and Pt / SrTiO3, etc.
[0004] To date, most catalysts for plastic pyrolysis involve the use of precious metals, which significantly increases costs, highlighting the urgent need to develop a novel and efficient catalytic system. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems of insufficient liquid phase yield and high calorific value in the existing low-density polyethylene (LDPE) pyrolysis process, and to provide a LDPE pyrolysis method and pyrolysis gasoline. This invention uses a specific ZSM-5 molecular sieve as a catalyst for LDPE pyrolysis, which has the advantages of high liquid phase yield and high liquid phase calorific value.
[0006] To achieve the above objectives, the first aspect of the present invention provides a method for pyrolyzing low-density polyethylene, the method comprising: pyrolyzing low-density polyethylene in the presence of H-type ZSM-5 molecular sieve;
[0007] The ZSM-5 molecular sieve has a silica-alumina molar ratio of 20-100.
[0008] In the X-ray diffraction pattern of the ZSM-5 molecular sieve, 2 θ The strongest diffraction peak in the range of 7.5° to 25° is I0, where I1 to I4 represent the four strongest diffraction peaks in the range of 7.5° to 25°, excluding I0, with 2θ increasing sequentially. Specifically, 0.45≤I1 / I0≤0.56, 0.53≤I2 / I0≤0.71, 0.42≤I3 / I0≤0.55, and 0.30≤I4 / I0≤0.39.
[0009] A second aspect of the present invention provides a pyrolysis gasoline prepared by the pyrolysis method described in the present invention.
[0010] Through the above technical solution, the present invention uses a specific ZSM-5 molecular sieve as a catalyst for the cracking of low-density polyethylene, which has the advantages of high liquid phase yield and high liquid phase combustion calorific value.
[0011] The low-density polyethylene pyrolysis method described in this invention enables the upgrading and recycling of polyolefin plastics into liquid fuel through a catalytic method under mild conditions without precious metals or external hydrogen. Attached Figure Description
[0012] Figure 1 This is an X-ray diffraction (XRD) image of ZSM-5 molecular sieve particles, as shown in Comparative Example 1.
[0013] Figure 2 This is an X-ray diffraction (XRD) image of ZSM-5 molecular sieve particles in Comparative Example 2;
[0014] Figure 3 The image shows the X-ray diffraction (XRD) image of the ZSM-5 molecular sieve particles prepared in Comparative Example 3.
[0015] Figure 4 The image shows the X-ray diffraction (XRD) image of the ZSM-5 molecular sieve particles prepared in Comparative Example 4.
[0016] Figure 5 These are X-ray diffraction (XRD) images of ZSM-5 molecular sieve particles prepared in Example 1;
[0017] Figure 6 These are X-ray diffraction (XRD) images of ZSM-5 molecular sieve particles prepared in Example 2;
[0018] Figure 7 The image shows a scanning electron microscope (SEM) image of the ZSM-5 molecular sieve particles prepared in Comparative Example 3.
[0019] Figure 8 This is a scanning electron microscope (SEM) image of the ZSM-5 molecular sieve particles prepared in Comparative Example 4;
[0020] Figure 9 These are scanning electron microscope (SEM) images of ZSM-5 molecular sieve particles prepared in step 1;
[0021] Figure 10 This is a scanning electron microscope (SEM) image of the ZSM-5 molecular sieve particles prepared in step 2. Detailed Implementation
[0022] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0023] In the context of this invention, including the following embodiments, the structure of ZSM-5 molecular sieve was characterized using a Bruker AXS D8 Advance instrument (Germany), and X-ray powder diffraction patterns were obtained. Cu-Ka radiation (λ = 0.15406 nm) was used, with an operating current of 100 mA and a voltage of 40 kV. The scanning range was 2θ = 5–40°, and the scanning rate was 5° / min.
[0024] The first aspect of the present invention provides a method for pyrolyzing low-density polyethylene, the method comprising: pyrolyzing low-density polyethylene in the presence of H-type ZSM-5 molecular sieve;
[0025] The silicon-aluminum molar ratio of the ZSM-5 molecular sieve is 20-100;
[0026] In the X-ray diffraction pattern of the ZSM-5 molecular sieve, 2 θ The strongest diffraction peak in the range of 7.5° to 25° is I0, where I1 to I4 represent the four strongest diffraction peaks in the range of 7.5° to 25°, excluding I0, with 2θ increasing sequentially. Specifically, 0.45≤I1 / I0≤0.56, 0.53≤I2 / I0≤0.71, 0.42≤I3 / I0≤0.55, and 0.30≤I4 / I0≤0.39. Using the ZSM-5 molecular sieve described in this invention as a catalyst for the pyrolysis of low-density polyethylene has the advantages of high liquid phase yield and high calorific value of liquid phase combustion. The low-density polyethylene pyrolysis method described in this invention can realize a catalytic method under mild conditions without precious metals or external hydrogen, upgrading and recycling polyolefin plastics into liquid fuel oil.
[0027] In the context of this specification, including the following embodiments, the silicon-aluminum molar ratio refers to the molar ratio of silicon dioxide to aluminum oxide.
[0028] According to a preferred embodiment of the present invention, 2θ of I0 is 7.91° ± 0.02°.
[0029] According to a preferred embodiment of the present invention, 2θ of I1 is 8.77° ± 0.03°.
[0030] According to a preferred embodiment of the present invention, 2θ of I2 is 22.70°±0.02° or 23.10°±0.02°.
[0031] According to a preferred embodiment of the present invention, 2θ of I3 is 22.90°±0.02° or 23.28°±0.02°.
[0032] According to a preferred embodiment of the present invention, 2θ of I4 is 23.52°±0.02° or 23.93°±0.02°.
[0033] According to a preferred embodiment of the present invention, the 2θ of I0 is 7.91° ± 0.02°; the 2θ of I1 is 8.77° ± 0.03°; the 2θ of I2 is 23.10° ± 0.02°; the 2θ of I3 is 23.28° ± 0.02°; and the 2θ of I4 is 23.93° ± 0.02°. This is beneficial for improving the liquid phase yield and the calorific value of liquid phase combustion in the pyrolysis products.
[0034] In this invention, there is no particular limitation on the preparation method of the ZSM-5 molecular sieve; as long as it possesses the aforementioned characteristics, the objective of this invention can be achieved. According to one embodiment of this invention, a method for preparing the ZSM-5 molecular sieve is provided, the method comprising:
[0035] The silicon-aluminum molar ratio of ZSM-5 molecular sieve is 20-100, the aluminum source is counted in molar amounts of aluminum atoms, the molar ratio of aluminum source to tetraalkylammonium hydroxide is 1:0.5-8, and the molar ratio of aluminum source to water is 1:100-1000. The aluminum source, silicon source, tetraalkylammonium hydroxide (e.g., tetrapropylammonium hydroxide) and water are mixed, crystallized, separated, washed, dried and calcined.
[0036] In this invention, the range of selectable crystallization conditions is relatively wide. According to a preferred embodiment of this invention, the crystallization conditions include: a crystallization temperature of 150-200℃ and a crystallization time of 2-5 days. In this embodiment of the invention, a crystallization reaction at 180℃ for 3 days is used as an example.
[0037] The present invention does not have any particular limitation on the drying conditions, as long as the water is removed. In the embodiments of the present invention, drying at 100°C for 12 hours is used as an example.
[0038] In this invention, the range of selectable calcination conditions is relatively wide. According to a preferred embodiment of this invention, the calcination conditions include: a calcination temperature of 500-600℃ and a calcination time of 3-10h. In this embodiment of the invention, air calcination at 600℃ for 5h is used as an example.
[0039] In this invention, the pyrolysis is carried out under non-hydrogen-dependent conditions. In this invention, non-hydrogen-dependent conditions mean that no hydrogen donor is added during the pyrolysis process; for example, no hydrogen, methane, ethane, propane, butane, pentane, ethylene, propylene, butene, pentene, or diene is introduced as a hydrogen donor.
[0040] According to a preferred embodiment of the present invention, the pyrolysis is carried out in an inert gas atmosphere, preferably, the inert gas is selected from argon and / or nitrogen.
[0041] In this invention, there are no particular limitations on the pyrolysis conditions. Conventional pyrolysis conditions in the art can be used in this invention. The pyrolysis method described in this invention can be carried out under relatively mild conditions. According to a preferred embodiment of this invention, the pyrolysis conditions include: 380-420°C, pressure of 0.5-1 MPa, and time of 0.5-2 h.
[0042] In this invention, there is no particular limitation on the ratio of ZSM molecular sieve to low-density polyethylene. Conventional amounts in the art can be used in this invention. According to a preferred embodiment of this invention, the mass ratio of ZSM molecular sieve to low-density polyethylene is 1:4-10.
[0043] The ZSM-5 molecular sieve described in this invention is suitable for the pyrolysis of low-density polyethylene and has the advantages of high liquid phase yield and high liquid phase combustion calorific value.
[0044] According to a preferred embodiment of the present invention, the density of low-density polyethylene is 0.91-0.93 g / cm³. 3 .
[0045] According to a preferred embodiment of the present invention, the low-density polyethylene has a melt index of 18-35 g / 10 min (190℃ / 2.16 kg) and a weight-average molecular weight of 50,000-200,000 g / mol.
[0046] Melt index represents the mass of melt passing through a capillary in 10 minutes at a standard temperature (190°C) and a load (2.16 kg) (unit: g / 10 min).
[0047] A second aspect of the present invention provides a pyrolysis gasoline prepared by the pyrolysis method described in the present invention.
[0048] According to a preferred embodiment of the present invention, the calorific value of the pyrolysis gasoline is 350 J / g or higher.
[0049] In the context of this invention specification, including the following embodiments, the calorific value was determined using a Mettler Toledo TGA / DSC 3+ simultaneous thermal analyzer. The sample was heated from room temperature to 600°C in the thermogravimetric analyzer at a rate of 15°C / min, with an air flow rate of 40 ml / min.
[0050] In this invention, the formulas for calculating the conversion rate of low-density polyethylene and the selectivity of liquid-phase products are as follows:
[0051] Low-density polyethylene conversion rate (%) = [1 - (Sresidual solids after reaction / Stotal solids before reaction)] × 100%
[0052] Liquid product selectivity (%) = (S_liquid mass / S_plastic mass) × 100%
[0053] The present invention will be described in detail below through embodiments.
[0054] In the following embodiments, the high-resolution field emission scanning electron microscope (FESSE) was used for testing with a JEOL Ltd. model JSM-IT800 instrument.
[0055] In the following examples and comparative examples, ZSM-5 molecular sieves were prepared into H-type ZSM-5 molecular sieves by ammonium exchange before use. Specifically, Na-type ZSM-5 molecular sieves were mixed and stirred with 2 mol / L ammonium chloride solution at 80°C for 6 hours, filtered, washed with deionized water, and the ammonium exchange was repeated 3 times. The mixture was dried at 100°C for 12 hours and then calcined in air at 600°C for 5 hours to obtain H-type ZSM-5 molecular sieves.
[0056] Comparative Example 1
[0057] ZSM-5 (SAR=25) molecular sieve was purchased from the catalyst factory of Nankai University; its morphology is hexagonal; its XRD image is as follows: Figure 1 As shown in the table below, the X-ray diffraction patterns of I0, I1, I2, I3, and I4, and their ratios, are as follows:
[0058] 2θ Peak Intensity I <![CDATA[I n / I0]]> <![CDATA[7.91899(I1)]]> 926 92% <![CDATA[8.81415(I2)]]> 551 55% <![CDATA[23.03938(I0)]]> 1004 100% <![CDATA[23.25344(I3)]]> 783 78% <![CDATA[23.87616(I4)]]> 516 51%
[0059] Catalyst evaluation: 2.5 g of H-type ZSM-5 molecular sieve was mixed with 20 g of LDPE (25 g / 10 min (190℃ / 2.16 kg), weight-average molecular weight MW = 58093 g / mol, density 0.92 g / cm³). 3 )
[0060] The mixture was thoroughly mixed and loaded into a reaction vessel. A 90-minute heat preservation test was conducted under an atmosphere of 380℃ and 0.5MPa argon gas. The test results are shown in Table 1.
[0061] Comparative Example 2
[0062] ZSM-5 (SAR=30) molecular sieve was purchased from Raodong Catalyst Factory, and its morphology is ellipsoidal.
[0063] Its XRD image is as follows Figure 2 As shown in the table below, the X-ray diffraction patterns of I0, I1, I2, I3, and I4, and their ratios, are as follows:
[0064] 2θ Peak Intensity I <![CDATA[I n / I0]]> <![CDATA[7.91899(I1)]]> 636 99% <![CDATA[8.77523(I2)]]> 436 68% <![CDATA[23.03938(I0)]]> 644 100% <![CDATA[23.25344(I3)]]> 444 69% <![CDATA[23.87616(I4)]]> 351 55%
[0065] Catalyst evaluation: 2.5 g of H-type ZSM-5 molecular sieve was reacted with 20 g of LDPE (25 g / 10 min (190℃ / 2.16 kg), MW = 58093 g / mol, density 0.92 g / cm³). 3 The mixture was thoroughly mixed and loaded into a reaction vessel. A heat preservation test was conducted for 90 minutes under an atmosphere of 380℃ and 0.5MPa argon gas. The test results are shown in Table 1.
[0066] Example 1
[0067] 0.44 g of sodium aluminate, 11.4 g of TPAOH aqueous solution (TPAOH content 25 wt%), and 30 g of deionized water were mixed evenly. Then, 20 g of TEOS was slowly added dropwise, and the mixture was stirred for 4 hours. The mixture was then sealed and heated to 180 °C for crystallization reaction for 3 days. The deionized water was filtered, dried at 100 °C for 12 hours, and then calcined in air at 600 °C for 5 hours to obtain Na-type ZSM-5 molecular sieve with a silica-alumina ratio of 40.
[0068] SEM image of ZSM-5 molecular sieve as shown below Figure 9 As shown, the XRD image of ZSM-5 molecular sieve is as follows: Figure 5 As shown in the table below, the X-ray diffraction patterns of I0, I1, I2, I3, and I4, and their ratios, are as follows:
[0069]
[0070]
[0071] Catalyst evaluation: 2.5 g of H-type ZSM-5 molecular sieve was reacted with 20 g of LDPE (25 g / 10 min (190℃ / 2.16 kg), MW = 58093 g / mol, density 0.92 g / cm³). 3 The mixture was thoroughly mixed and loaded into a reaction vessel. A heat preservation test was conducted for 90 minutes under an atmosphere of 380℃ and 0.5MPa argon gas. The test results are shown in Table 1.
[0072] Example 2
[0073] 0.22 g sodium aluminate, 11.4 g TPAOH aqueous solution (TPAOH content 25 wt%), and 30 g deionized water were mixed evenly. Then, 20 g TEOS was slowly added dropwise, and the mixture was stirred for 4 hours. The mixture was then sealed, heated to 180°C, and kept at that temperature for 3 days. The deionized water was filtered, dried at 100°C for 12 hours, and then calcined in air at 600°C for 5 hours to obtain Na-type ZSM-5 molecular sieve with a silica-to-alumina ratio of 80.
[0074] SEM image of ZSM-5 molecular sieve as shown below Figure 10 As shown, the XRD image of ZSM-5 molecular sieve is as follows: Figure 6 As shown in the table below, the X-ray diffraction patterns of I0, I1, I2, I3, and I4, and their ratios, are as follows:
[0075] 2θ Peak Intensity I <![CDATA[I n / I0]]> <![CDATA[7.91899(I0)]]> 1140 100% <![CDATA[8.79469(I1)]]> 640 56% <![CDATA[23.09776(I2)]]> 810 71% <![CDATA[23.2729(I3)]]> 631 55% <![CDATA[23.93454(I4)]]> 441 39%
[0076] Catalyst evaluation: 2.5 g of H-type ZSM-5 molecular sieve was reacted with 20 g of LDPE (25 g / 10 min (190℃ / 2.16 kg), MW = 58093 g / mol, density 0.92 g / cm³). 3 The mixture was thoroughly mixed and loaded into a reaction vessel. A heat preservation test was conducted for 90 minutes under an atmosphere of 380℃ and 0.5MPa argon gas. The test results are shown in Table 1.
[0077] Comparative Example 3
[0078] A sol-gel solid was prepared by dissolving silica solution (Ludox HS-40), deionized water, sodium hydroxide, and sodium aluminate. The specific steps were as follows: 40g of Ludox HS-40 was slowly added dropwise to an 80℃, 2mol / L sodium hydroxide solution (18.66ml water, 0.7464g sodium hydroxide), and stirred until the solution became clear, yielding solution A. 1.2g of sodium aluminate was dissolved in the 2mol / L sodium hydroxide solution (18.66ml water, 0.7464g sodium hydroxide), and stirred until clear, yielding solution B. Solution B was slowly added dropwise to solution A, and after mixing, an aluminosilicate gel was obtained. The mixture was vigorously stirred at 100℃ and kept at that temperature for 2 hours. The gel was then transferred to a sealed reactor, heated to 180℃, and reacted for 48 hours. Subsequently, it was dried at 100℃ for 12 hours, and then calcined in air at 600℃ for 6 hours to obtain a Na-type ZSM-5 molecular sieve with a silica-to-alumina ratio of 40.
[0079] SEM image of ZSM-5 molecular sieve as shown below Figure 7 As shown, the XRD image of ZSM-5 molecular sieve is as follows: Figure 3 As shown in the table below, the X-ray diffraction patterns of I0, I1, I2, I3, and I4, and their ratios, are as follows:
[0080] 2θ Peak Intensity I <![CDATA[I n / I0]]> <![CDATA[7.91899(I1)]]> 788 98% <![CDATA[8.79469(I2)]]> 488 61% <![CDATA[23.05884(I0)]]> 801 100% <![CDATA[23.23398(I3)]]> 561 70% <![CDATA[23.89562(I4)]]> 389 49%
[0081] Catalyst evaluation: 2.5 g of H-type ZSM-5 molecular sieve was reacted with 20 g of LDPE (25 g / 10 min (190℃ / 2.16 kg), MW = 58093 g / mol, density 0.92 g / cm³). 3 The mixture was thoroughly mixed and loaded into a reaction vessel. A heat preservation test was conducted for 90 minutes under an atmosphere of 380℃ and 0.5MPa argon gas. The test results are shown in Table 1.
[0082] Comparative Example 4
[0083] The method of Example 2 was followed, except that the amount of sodium aluminate was replaced from 0.22 g to 1.31 g, while the other conditions were the same as in Example 2. Na-type ZSM-5 molecular sieves were obtained with a silica-alumina ratio of 12.
[0084] SEM image of ZSM-5 molecular sieve as shown below Figure 8 As shown, the XRD image of ZSM-5 molecular sieve is as follows: Figure 4 As shown in the table below, the X-ray diffraction patterns of I0, I1, I2, I3, and I4, and their ratios, are as follows:
[0085] 2θ Peak Intensity I <![CDATA[I n / I0]]> <![CDATA[7.89953(I0)]]> 1131 100% <![CDATA[8.77523(I1)]]> 630 56% <![CDATA[23.05884(I2)]]> 620 55% <![CDATA[23.23398(I3)]]> 329 29% <![CDATA[23.93454(I4)]]> 315 28%
[0086] Catalyst evaluation: 2.5 g of H-type ZSM-5 molecular sieve was reacted with 20 g of LDPE (25 g / 10 min (190℃ / 2.16 kg), MW = 58093 g / mol, density 0.92 g / cm³). 3 The mixture was thoroughly mixed and loaded into a reaction vessel. A heat preservation test was conducted for 90 minutes under an atmosphere of 380℃ and 0.5MPa argon gas. The test results are shown in Table 1.
[0087] Example 3
[0088] The ZSM-5 molecular sieve prepared according to the method in Example 2 was used as a catalyst, with the difference being...
[0089] 2.5g of H-type ZSM-5 molecular sieve was mixed with 20g of LDPE (18g / 10min (190℃ / 2.16kg), MW=155000g / mol, density 0.924g / cm³). 3 The mixture was thoroughly mixed and placed into a reaction vessel. A heat preservation test was conducted at 420℃ and under an argon atmosphere of 0.5MPa for 30 minutes. The test results are shown in Table 1.
[0090] Example 4
[0091] The ZSM-5 molecular sieve prepared according to the method in Example 2 was used as a catalyst, with the difference being...
[0092] 2.5g of H-type ZSM-5 molecular sieve was mixed with 10g of LDPE (25g / 10min (190℃ / 2.16kg), MW=145000g / mol, density 0.923g / cm³). 3 The mixture was thoroughly mixed and placed into a reaction vessel. A 90-minute heat preservation test was conducted under an atmosphere of 400℃ and 1.0MPa argon gas. The test results are shown in Table 1.
[0093] Example 5
[0094] 0.7 g sodium aluminate, 11.4 g TPAOH aqueous solution (TPAOH content 25 wt%), and 30 g deionized water were mixed evenly. Then, 20 g TEOS was slowly added dropwise, and the mixture was stirred for 4 hours. The mixture was then sealed, heated to 180°C, and kept at that temperature for 3 days. The deionized water was filtered, dried at 100°C for 12 hours, and then calcined in air at 600°C for 5 hours to obtain Na-type ZSM-5 molecular sieve with a silica-to-alumina ratio of 27.
[0095] The X-ray diffraction patterns of ZSM-5 molecular sieves, including I0, I1, I2, I3, I4, and their ratios, are shown in the table below:
[0096] 2θ Peak Intensity I <![CDATA[I n / I0]]> <![CDATA[7.92008(I0)]]> 1026 100% <![CDATA[8.78557(I1)]]> 503 49% <![CDATA[23.1025(I2)]]> 608 59% <![CDATA[23.2693(I3)]]> 496 48% <![CDATA[23.94027(I4)]]> 368 36%
[0097] Catalyst evaluation: 2.5 g of H-type ZSM-5 molecular sieve was mixed with 25 g of LDPE (25 g / 10 min (190℃ / 2.16 kg), MW = 58093 g / mol, density 0.92 g / cm³). 3 The mixture was thoroughly mixed and loaded into a reaction vessel. A heat preservation test was conducted for 90 minutes under an atmosphere of 380℃ and 0.5MPa argon gas. The test results are shown in Table 1.
[0098] Comparative Example 5
[0099] The ZSM-5 molecular sieve prepared according to the method in Example 2 was used as the catalyst, except that high-density polyethylene (melt index 7.2 g / 10 min, MW = 70665 g / mol, density 0.951 g / cm³) was used. 3 The low-density polyethylene was replaced with another polyethylene, and the other conditions were the same as in Example 2. The test results are shown in Table 1.
[0100] Table 1
[0101] serial number Conversion rate Liquid phase product selectivity Calorific value of liquid phase products Comparative Example 1 66.65% 34.80% 320.14 J / g Comparative Example 2 97.50% 32.20% 332.74 J / g Comparative Example 3 61.45% 29.20% 307.23 J / g Comparative Example 4 50.85% 26.30% 314.08 J / g Comparative Example 5 90.30% 30.60% 347.06 J / g Example 1 92.25% 37.50% 354.80 J / g Example 2 99.75% 43.75% 381.26 J / g Example 3 98.37% 37.57% 351.37 J / g Example 4 99.53% 39.39% 365.35J / g Example 5 96.62% 41.27% 359.72 J / g
[0102] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for pyrolyzing low-density polyethylene, characterized in that, The method includes: pyrolyzing low-density polyethylene in the presence of H-type ZSM-5 molecular sieve; The silicon-aluminum molar ratio of the ZSM-5 molecular sieve is 20-100; In the X-ray diffraction pattern of the ZSM-5 molecular sieve, 2 θ The strongest diffraction peak in the range of 7.5° to 25° is I0, where I1 to I4 represent the four strongest diffraction peaks in the range of 7.5° to 25°, excluding I0, with 2θ increasing sequentially. Specifically, 0.45≤I1 / I0≤0.56, 0.53≤I2 / I0≤0.71, 0.42≤I3 / I0≤0.55, and 0.30≤I4 / I0≤0.
39.
2. The pyrolysis method according to claim 1, wherein, I0's 2θ = 7.91° ± 0.02°; and / or I1's 2θ = 8.77° ± 0.03°; and / or I² = 22.70° ± 0.02° or 23.10° ± 0.02°; and / or I3's 2θ = 22.90° ± 0.02° or 23.28° ± 0.02°; and / or The 2θ of I4 is 23.52° ± 0.02° or 23.93° ± 0.02°.
3. The pyrolysis method according to claim 1 or 2, wherein, 2θ = 7.91° ± 0.02° for I0; 2θ = 8.77° ± 0.03° for I1; 2θ = 23.10° ± 0.02° for I2; 2θ = 23.28° ± 0.02° for I3; 2θ = 23.93° ± 0.02° for I4.
4. The pyrolysis method according to claim 1 or 2, wherein, 0.49≤I1 / I0≤0.56, 0.59≤I2 / I0≤0.71, 0.48≤I3 / I0≤0.55, 0.36≤I4 / I0≤0.
39.
5. The pyrolysis method according to claim 1 or 2, wherein, The pyrolysis was carried out under non-hydrogen-contaminated conditions.
6. The pyrolysis method according to claim 5, wherein, The pyrolysis is carried out in an inert gas atmosphere, the inert gas being selected from argon and / or nitrogen.
7. The pyrolysis method according to claim 1 or 2, wherein, The pyrolysis conditions include: a temperature of 380-420℃, a pressure of 0.5-1MPa, and a time of 0.5-2h.
8. The pyrolysis method according to claim 1 or 2, wherein, The mass ratio of ZSM-5 molecular sieve to low-density polyethylene is 1:4-10.
9. The pyrolysis method according to claim 1 or 2, wherein, The low-density polyethylene has a density of 0.91-0.93 g / cm³. 3 ; Preferably, the low-density polyethylene has a melt index of 18-35 g / 10 min and a weight-average molecular weight of 50,000-200,000 g / mol.
10. The pyrolysis oil prepared by the pyrolysis method according to any one of claims 1-9, preferably, the pyrolysis gasoline has a calorific value of 350 J / g or higher.
Citation Information
Cited By
Hydrocracking catalyst, preparation method and application thereof, and low-density polyethylene hydrocracking method
CN121060592A
Hydrocracking catalyst, process for its preparation and use, and process for the hydrocracking of low density polyethylene
CN121060592B